2022
DOI: 10.35882/jeeemi.v4i3.241
|View full text |Cite
|
Sign up to set email alerts
|

Design And Fabrication of Temperature and Humidity Stabilizer on Low Voltage Distribution Panel with PLC-Based Fuzzy Method to Prevent Excessive Temperature and Humidity on The Panel

Abstract: Distribution panel is equipment that functions to receive electrical energy from PLN and subsequently distributes, as well as controls the distribution of electrical energy through the main and branch panel circuits to branch Distribution Panel or directly through the final load circuit. One of the problems with the Distribution Panel is the occurrence of fluctuating voltage changes and disturbances caused by condensation due to high humidity values. Based on previous research, the solution to minimize this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Corona causes insulation failure in the air because the air around the conductor or conductor is ionized. Many previous studies have examined controlling temperature and humidity in cubicles using fans and heaters, but the temperature and humidity have not yet reached a stable and optimal point [8]. The corona effect on cubicle terminations that can trigger disturbances such as a decrease in insulation quality, power losses, and a large increase in harmonic distortion can be stabilized and optimized with this research.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Corona causes insulation failure in the air because the air around the conductor or conductor is ionized. Many previous studies have examined controlling temperature and humidity in cubicles using fans and heaters, but the temperature and humidity have not yet reached a stable and optimal point [8]. The corona effect on cubicle terminations that can trigger disturbances such as a decrease in insulation quality, power losses, and a large increase in harmonic distortion can be stabilized and optimized with this research.…”
Section: Discussionmentioning
confidence: 96%
“…Based on research [8] one way to optimize the temperature and humidity values in the cubicle is to use a fan and heater. Fan and heater control is carried out based on the temperature and humidity values on the panel that are read on the sensor [9].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated humidity levels can cause condensation on electrical components. This moisture can lead to short circuits, fluctuating voltage changes, and even equipment failure, posing significant risks [2]. This may also lead to corrosion of materials.…”
Section: Humidity-induced Disturbancesmentioning
confidence: 99%
“…Another study designed and fabricated a temperature and humidity stabilizer on a low voltage distribution panel with a PLC-based fuzzy method to prevent excessive temperature and humidity on the panel. The study found that fan control using the fuzzy method could reduce the temperature faster than fan control with simple logic [8].…”
Section: Introductionmentioning
confidence: 99%